Measurements of leaf area index using optical method (IAI-2000) in oil palm plantation: accuracy and limitation assessment - Awal, Md Abdul; Wan Ismail, Wan Ishak; Endan, Johari; Harun, Mohd Haniff (Universiti Putra Malaysia Press, 2006)
Leaf area index (LAI) is an important parameter for characterizing the canopy structure ofa crop. The LAI, which is often used as a critical variable to simulate different ecosystem models, is difficult to measure directly in oil palm. In this study, optical methods for quantifYing variation in LAI under different conditions were evaluated. It was found that the accuracy of the readings depended on different factors, such as measuring technique, view cap angle, spatial variability, and height of the measuring point. The measuring technique had an effect on the LAI measurement. Results showed that the Zigzag method underestimated the LAI compared to other methods. The LAI by the Zigzag method was 11.6% less than the LAI by the "one above and four below" technique and 5.7% less than the LAI by the "one above and eight below" technique. The LAI obtained I7y the "one above eight below" technique was 6.2% less than the LAI obtained with the "one abovefour below" technique. Results from the investigation ofthe effect of view cap on LAI measurement showed that the view cap strongly influenced the LAI calculation and LAI decreased with increase in the view cap angle. PCA LAI values were also affected by spatial variability and height of the sensor. PCA LAI values increased with increase in sensor height above ground with a maximum LAI value (2.77) at 2.5-meter height above ground and mzmmum LAI value (0.932) at O-meter height from ground. Maximum values of LAI were obtained for all dIrectIOns at 0.5-meter dtstance from the trunk and minimum LA1 values were obtained near the tip of the frond. The PCA LAI values increased by about 5%- 50% with increase in distance from the frond tip to frond base.